How you perceive threat determines your behavior - Junior, Orlando F.; Portugal, Liana C.; Alves, Rita d.; Campagnoli, Rafaela R.; Erthal, Fátima C.; Mocaiber, Izabela F.; David, Isabel A.; Volchan, Eliane; Oliveira, Leticia; Pereira, Mirtes G. (Frontiers in Human Neuroscience, 2013)
The prioritization of processing emotional stimuli usually produces deleterious effects on task performance when it distracts from a task. One common explanation is that brain resources are consumed by emotional stimuli, diverting resources away from executing the task. Viewing unpleasant stimuli also generates defensive reactions, and these responses may be at least partially responsible for the effect of the emotional modulation observed in various reaction time (RT) paradigms. We investigated whether modulatory effects on RT vary if we presented threat stimuli to prompt different defensive responses. To trigger different responses, we manipulated threat perception by moving the direction of threatening stimuli. Threatening or neutral stimuli were presented as distractors during a bar orientation discrimination task. The results demonstrated that threat stimuli directed towards the observer produced a decrease in RT; in contrast, threat stimuli directed away from the observer produced an increase in RT, when compared to neutral stimuli. Accelerated RT during direct threat stimuli was attributed to increased motor preparation resulting from strong activation of the defense response cascade. In contrast, no direct threat stimuli likely activated the defense cascade, but less intensively, prompting immobility. Different threat stimuli produced varying effects, which was interpreted as evidence that the modulation of RT by emotional stimuli represents the summation of attentional and motivational effects. Additionally, participants who had been previously exposed to diverse types of violent crime were more strongly influenced by direct threat stimuli. In sum, our data support the concept that emotions are indeed action tendencies.